Peran Biro Perjalanan Wisata dalam Mewujudkan Pariwisata Berkelanjutan di Taman Nasional Taka Bonerate - Berliani Berliani; Darmayasa Darmayasa; Margaretha Wadid Rante; yenni susanto (ITINERARY: Journal of Travel Operation and Travel Business, 2025)
Taka Bonerate National Park in South Sulawesi, Indonesia, is a renowned marine tourism destination famous for its coral reefs and marine biodiversity. This study aims to analyze the role of travel agencies in promoting sustainable tourism, particularly in the context of diving activities. Using a qualitative approach, this research involved interviews with tourists and travel agencies, as well as field observations to explore tourist experiences and strategies implemented by travel agencies. The results show that although travel agencies have integrated sustainability principles into their operations, significant challenges remain in waste management and tourist activity supervision. Promotion based on natural beauty and collaboration with local dive centers have proven effective in attracting tourists; however, the lack of education and environmentally friendly facilities at tourist sites remains a major obstacle. This study contributes to understanding the role of travel agencies in supporting sustainable tourism, emphasizing the need for closer collaboration between travel agencies, local communities, and the government. The findings also highlight the importance of increased supervision and tourist education to maintain environmental conservation